2023
DOI: 10.1101/2023.02.23.529799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parental childhood maltreatment associates with offspring left amygdala volume at early infancy

Abstract: Background: Childhood maltreatment exposure (CME) and related trauma could be considered some of psychiatry's greatest public health challenges. CME and early adversity have been associated with increased amygdala volume in exposed individuals. Emerging evidence implies that CME could also affect prenatal development of the offspring. Methods: As part of the FinnBrain Birth Cohort Study, we measured bilateral amygdala volumes from MR images in 76 healthy infants at 2 to 5 weeks of gestation corrected age and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(70 reference statements)
2
1
0
Order By: Relevance
“…In a study of infants in the first two years of life, Khoury et al (2021) reported that infants of mothers with a childhood history of maltreatment had lower gray matter volume and lower amygdala volume. Similar (but not identical) findings were reported in a Finnish cohort by Tuulari et al (2023) using similar methods. Specifically, maternal childhood maltreatment was associated with infants' greater left (but not right) amygdala volume.…”
Section: Studies Of the Intergenerational Transmission Of Traumasupporting
confidence: 85%
“…In a study of infants in the first two years of life, Khoury et al (2021) reported that infants of mothers with a childhood history of maltreatment had lower gray matter volume and lower amygdala volume. Similar (but not identical) findings were reported in a Finnish cohort by Tuulari et al (2023) using similar methods. Specifically, maternal childhood maltreatment was associated with infants' greater left (but not right) amygdala volume.…”
Section: Studies Of the Intergenerational Transmission Of Traumasupporting
confidence: 85%
“…Prior studies and the current study identified sperm epigenetic features that could potentially have effects on offspring brain development, which ties in with our recent neuroimaging studies that link paternal CME with offspring neonate brain structure (H. Karlsson et al, 2020;Tuulari, Kataja, Karlsson, & Karlsson, 2022;Tuulari et al, 2023). Several studies, including from our group, have identified that lifestyle factors remodel DNA methylation near genes controlling the development of the brain in human sperm (Donkin et al, 2016;Ingerslev et al, 2018), supporting that genomic regions involved in brain development are hotspots of epigenetic variation in response to environmental stress.…”
Section: Epigenetic Measuressupporting
confidence: 67%
“…In a small FinnBrain study (n = 72), paternal early life stress was associated with increased FA values in the body of the corpus callosum, right superior corona radiata, and parts of the internal capsule, 103 even when controlling for confounders including maternal early life stress, maternal SES, or prenatal depression. A recent preprint 104 reported positive associations between maternal (but not paternal) childhood maltreatment and infant left amygdala volume. In an exploratory analysis, the timing of exposure was considered, with increased left amygdala volume observed in infants whose mothers experienced childhood maltreatment between ages 13 and 18, and in those whose fathers experienced this between ages 0 and 6.…”
Section: Maternal Stress During Pregnancymentioning
confidence: 94%